Bildung in Deutschland 2016 Ein indikatorengestützter Bericht mit einer Analyse zu Bildung und Migration - Bildungsberichterstattung, Autorengruppe (W. Bertelsmann Verlag, 2016)
"In the long-term observation of the German education system, the authors proceeded to analyse the known indicators of the study. A key topic is the influence of migration experiences on educational biography. Every two years, the report delivers a survey of the German education system and examines framework conditions, such as costs and requirements, educational institutions like nurseries and schools, vocational training and university education, further education at an adult age and educational effects and returns."